Utilization of The Built-up Index to Measure Temporal Changes in the Slow Cities (Cittaslow) in Turkey - Salman Özüpekçe (Coğrafya Dergisi)
The cities in Turkey are currently witnessing rapid, unplanned expansion, which needs to be regulated . Cittaslow Network—which comprises initiatives such as the prioritization of infrastructural projects, precise planning of sustainable cities , facilities to support people with disabilities, and the provision of renewable and eco-energy for vehicles—has the potential to facilitate better planning of the slow cities in Turkey. To control unplanned urban expansion and overcome infrastructural deficits, participation of the citizens in the Cittaslow Network is important in the rapidly expanding Turkish cities. Although Turkey currently has 18 slow cities, many other Turkish cities are undergoing the application process to qualify under this criterion. The built-up index, which is rarely opted for by researchers in Turkey but frequently used in studies abroad, has been used in this research. The built-up index is a model that extracts urban areas from satellite data. This model determines micro-urban structures and demonstrates the extent of urbanization. The temporal changes observed in 17 Cittaslow Cities in Turkey from 2002 to 2020 were examined in this research. The findings reveal that slow cities such as Yalvaç, Akyaka, and Gökçeada are expanding rapidly, whereas Cittaslow cities such as Vize, Uzundere, Göynük, and Eğirdir have been experiencing slow growth.